Clinical and genetic features of patients with facial‐sparing facioscapulohumeral muscular dystrophy. (21st December 2017) - He, J.‐J.; Lin, X.‐D.; Lin, F.; Xu, G.‐R.; Xu, L.‐Q.; Hu, W.; Wang, D.‐N.; Lin, H.‐X.; Lin, M.‐T.; Wang, N.; Wang, Z.‐Q.
Abstract : Background and purpose: Facial‐sparing scapular myopathy (SHD) is the most common atypical form of facioscapulohumeral muscular dystrophy (FSHD), clinically defined as without apparent facial muscle weakness on neurological examination. The clinical profiles and genetic features of SHD are limited. Methods: A cohort of 21 Chinese patients with SHD were confirmed by molecular genetic analysis based on pulsed‐field gel electrophoresis. The clinical assessments and methylation analysis were noted. Results: The patients had FSHD‐related EcoRI fragments with 4qA haplotype ranging from 18 kb to 33 kb (mean 26.3 ± 4.6 kb). The mean onset age was 25.52 ± 8.3 years. Over half of the patients had scapular winging and asymmetry weakness consistent with FSHD, without facial symptoms during their visit. Their facial electromyogram results were almost normal or mild myogenic damage, as well as the myopathology and serum creatine kinase. A conflict was unexpectedly found in intergenerational DR1 methylation analysis. Conclusion: Facial‐sparing scapular myopathy is characterized as mild myopathic symptoms and chronic progression of weakness. The diagnosis should be accurately confirmed through FSHD‐sized fragment detection and 4qA/B variant determination. Although the next generations of SHD had more severe muscular symptoms, local hypomethylation within D4Z4 was not found as a modifier for clinical heterogeneity.